THE POSITIVE INFLUENCE OF URBANIZATION ON ENERGY CONSUMPTION IN LATIN AMERICAN COUNTRIES: AN APPROACH WITH ARDL AND NARDL MODELING (Revista de Estudos Sociais, 2018)
The impact of urbanization on energy consumption was investigated in eight Latin American countries from 1970 to 2015. The Autoregressive Distributed Lag (ARDL) in the form of Unrestricted Error Correction Model (UECM) to decompose the total effect of variables into it is short- and long-run components, and the Non-Linear Autoregressive Distributed Lag (NARDL) to examine the asymmetric responses of variables were applied. The results of preliminary tests indicated the existence of low multicollinearity, and existence of cross-section dependence. The results showed that in the ARDL model the economic growth in the short-and long-run increase the energy consumption, and the variable urbanization in the short-and long-run have a positive impact on energy used. Furthermore, the outcomes of NARDL model showed that in the short-and long-run asymmetric responses the economic growth (positive/negative asymmetric) have a positive impact on energy. The variable urbanization in the short-and long-run have a positive on energy consumption. Moreover, the specification tests showed the presence of cross-section dependence, the first-order autocorrelation, the heteroscedasticity in the residuals, and the first-order correlation in the disturbance, and serial correlation in the disturbance. Finally, this study points to the necessity to creates conservation policies oriented to reduces the energy consumption, with the introduction of new technologies that reduces the energy consumption in the industries and households, change the current energy matrix to a more sustainable.